2015
DOI: 10.4162/nrp.2015.9.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient composition of human milk from Korean mothers of full term infants born at 37-42 gestational weeks

Abstract: BACKGROUND/OBJECTIVESBreast milk is the best available food for optimum growth and development of infants and the breastfeeding rate is increasing in Korea. The purpose of this study is to measure the concentrations of macronutrients and to evaluate their changes according to lactation period in breast milk from lactating Korean women.SUBJECTS/METHODSMilk samples were obtained from 2,632 healthy lactating women (mean age; 32.0 ± 3.3 years), where the lactating period was up to a period of 8 months, who also vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
71
4
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 28 publications
(33 reference statements)
19
71
4
3
Order By: Relevance
“…In our analysis of macronutrients (P, C, F) in breast milk samples obtained during the fi rst month after delivery, we observed a decline in protein levels in time. Our fi ndings corresponded with the dynamics presented in other studies (12). Mature milk usually contains 0.9-1.2 g/dl of protein (2).…”
Section: Discusionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our analysis of macronutrients (P, C, F) in breast milk samples obtained during the fi rst month after delivery, we observed a decline in protein levels in time. Our fi ndings corresponded with the dynamics presented in other studies (12). Mature milk usually contains 0.9-1.2 g/dl of protein (2).…”
Section: Discusionsupporting
confidence: 91%
“…In samples from Mother 2, the fat content gradually rose from week 1, reached maximum of 5 g/dl in the 2nd week, and then decreased up to the 4th week. This fi nding does not correlate with the dynamics shown in other studies (12). In line with the study of Bauer and Gerss, 2011 (13), our study shows that the levels of carbohydrates in the samples from Mother 2 gradually increased.…”
Section: Discusionsupporting
confidence: 51%
“…The few earlier studies investigating relationships between protein content in human milk and maternal nutritional status are contradictory. Some reporting a positive correlation between protein and maternal adiposity assessed by BMI [2,7,12,21], whereas Quinn et al [23] and Kugananthan et al [17] have found that higher percentage of fat mass but not BMI was associated with higher protein concentrations. By contrast, Bachour et al [2] reported negative association between protein content and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The varied associations between milk macronutrients and maternal anemia parallel the wider literature on maternal undernutrition: Lönnerdal's seminal review published in 1986 argues that maternal malnutrition generally has little effect on total protein concentrations of milk. More recent studies, however, show a positive (Chang et al, ; Grote et al, ; Michaelsen, Skafte, Badsberg, & Jørgensen, ) or a negative (Bachour, Yafawi, Jaber, Choueiri, & Abdel‐Razzak, ) association between maternal protein‐energy status (BMI) and milk protein. Milk fat is similarly reported to have a positive association (Chang et al, ; Grote et al, ; Michaelsen et al, ; Nommsen, Lovelady, Heinig, Lönnerdal, & Dewey, ) or no association (Bachour et al, ; Mandel, Lubetzky, Dollberg, Barak, & Mimouni, ) with maternal protein‐energy deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies, however, show a positive (Chang et al, ; Grote et al, ; Michaelsen, Skafte, Badsberg, & Jørgensen, ) or a negative (Bachour, Yafawi, Jaber, Choueiri, & Abdel‐Razzak, ) association between maternal protein‐energy status (BMI) and milk protein. Milk fat is similarly reported to have a positive association (Chang et al, ; Grote et al, ; Michaelsen et al, ; Nommsen, Lovelady, Heinig, Lönnerdal, & Dewey, ) or no association (Bachour et al, ; Mandel, Lubetzky, Dollberg, Barak, & Mimouni, ) with maternal protein‐energy deficiency. Milk lactose has been described as the least affected by maternal nutritional status, yet a recent study reports a significant inverse relationship between BMI and lactose (Chang et al, ).…”
Section: Introductionmentioning
confidence: 99%